Short-term dietary restriction in old zebrafish changes cell senescence mechanisms. (15th October 2016) - Arslan-Ergul, Ayca; Erbaba, Begun; Karoglu, Elif Tugce; Halim, Dilara Ozge; Adams, Michelle M.
Highlights: Age but not short-term dietary restriction (DR) affects cell proliferation. Short-term DR shortens telomere lengths in young subjects. Impacts of DR may not always be beneficial for cellular senescence and organismal aging. First study to systematically examine a short-term DR in zebrafish. Abstract: Brain aging is marked by a decline in cognitive abilities and associated with neurodegenerative disorders. Recent studies have shown, neurogenesis continues into adulthood but is known to be decreasing during advancing age and these changes may contribute to cognitive alterations. Advances, which aim to promote better aging are of paramount importance. Dietary restriction (DR) is the only non-genetic intervention that reliably extends life- and health-span. Mechanisms of how and why DR and age affect neurogenesis are not well-understood, and have not been utilized much in the zebrafish, which has become a popular model to study brain aging and neurodegenerative disease due to widely available genetic tools. In this study we used young (8–8.5 months) and old (26–32.5 months) zebrafish as the model to investigate the effects of a short-term DR on actively proliferating cells. We successfully applied a 10-week DR to young and old fish, which resulted in a significant loss of body weight in both groups with no effect on normal age-related changes in body growth. We found that age decreased cell proliferation and increased senescence associated β-galactosidase, as well as shortened telomere lengths. In contrast, DR shortened telomere lengths only in young animals. Neither age nor DR changed the differentiation patterns of glial cells. Our results suggest that the potential effects of DR could be mediated by telomere regulation and whether these are beneficial or negative remains to be determined.